Cephalometric Comparison of Skeletal and Dental Characteristics between Typical Arab and Chinese Adults - Ali FR Rabah (AIMS Medical Science, 2017)
The purpose of this study was to determine the cephalometric norms of typical Arab young adults with class I molar relationship and well-balanced face and to compare these norms with those derived from matched Chinese subjects. Lateral cephalometric of 71 Arab adults (37 males age 20–26) (female age 20–26) were compared with 76 Chinese young adults (42 male age 20–26) (34 female 20–26).Each lateral cephalogram were traced and digitized using cephalometric software program according to Steiner analysis. Advanced maxilla and protruded mandible observed in Chinese sample compared with the Arab sample showed greater mean and standard deviation in SNA, SNB and ANB angles (p < 0.001). More proclination in upper and lower incisor teeth according to (U1/NA, L1/NA) angles observed in the Chinese sample, on the other hand, the mean value of MP/SN was higher in Arabs than that in Chinese (p < 0.001) showing more vertical growth and increased lower facial height. Also greater horizontal growth was observed in Arabs according to average value of SN/OP angle when compared to the Chinese sample (p < 0.001). There are some fundamental ethnic differences in the craniofacial and skeletal measurements between Arabs and Chinese young adult. Theses variations support the idea that a single standard in facial aesthetics should not be applied and used to all racial and ethnic groups. The results of this study showed that the Chinese’s Maxilla and Mandible were more protruded than Arabs, while Arabs had a higher angle of both the occlusal and mandibular planes.